Current practices of waste management in teaching hospitals and presence of incinerators in densely populated areas - Salma Khalid; Najibul Haq; Zia-; Abdul Latif; Muhammad Amjad Khan; Javaid Iqbal; Nowsher Yousaf (BMC, 2021)
Abstract Background Hospital waste management (HWM) practices are the core need to run a proper health care facility. This study encompasses the HWM practices in teaching hospitals of Peshawar, Pakistan and examine the enforcement of Pak HWM (2005) rules and risks through transmission of pathogens via blood fluids, air pollution during waste incineration and injuries occurring in conjunction with open burning and dumping. Methods A questionnaire based on World Health Organization (WHO) recommendations was used to survey the selected private and public teaching hospital (n = 16). Site visits and personnel observations were also included in the data. It was spatio-statistically analyzed using descriptive statistics, Krushkal-wallis and Fisher's exact tests. Results The findings revealed that the lack of HWM practices in all surveyed hospitals (p > 0.05), besides statistical difference (p < 0.017) in waste generation/day. No proper segregation of waste from generation point to final disposal was practiced. However, the performance of private teaching hospitals (50%) was found better in terms of HWM personnel and practices. In surveyed hospitals, only nine hospitals (56.3%) were found with the incinerator facility while rest of the hospitals (43.7%) practiced open dumping. Moreover, operational parameters of the incinerators were not found satisfactory and located in densely populated areas and emitting hazardous gases. Conclusion Proper HWM practices are not being followed in the light of WHO guidelines. Hospital waste impose serious menace to healthcare workers and to nearby population. WHO issued documents for improving HWM practices but triggered no change in Pakistan. To improve the situation, insights in this context is need for enforcement of rules.